Information System for Processing Police Report Data at the North Gorontalo Police Women and Children Protection Unit: Sistem Informasi Pengolahan Data Laporan Polisi Pada Unit Perlindungan Perempuan Dan Anak Polres Gorontalo Utara - Suleman, Fitriyanti; Tue, Noviyanti; Talib, Maryati Kadir (JOINCS (Journal of Informatics, Network, and Computer Science), 2023)
Designing an Information System for Processing Police Report Data at the Women and Children Protection Unit of the North Gorontalo Police, so that it can assist officers in collecting large numbers of reports, and can present reports quickly. The method used is the Research and Development (R&D) method. The system is made with PHP and HTML programming. The database used is the MySql language. For modeling using UML (Unified Modeling Language). For testing this system using white box and black box testing where with this test the correct graph flow is obtained as a sample the researcher tests the Input Data flowchart Report on the admin system obtained is the value of region (R) = 3, Independent path = 3, and Cyclomatic Complexity (CC) = 3.